Effect of different chelators on the push-out bond strength of hydraulic cements in retrograde obturation - Büşra Dağıstan-Çavuşoğlu; Sıla Nur Usta (Journal of Dental Research, Dental Clinics, Dental Prospects)
Background. This study examined the effect of ethylenediaminetetraacetic acid (EDTA) and etidronic acid (HEDP) in retrograde cavities on the bond strength of MTA Angelus and NeoPutty. Methods. Sixty-six teeth with single roots and canals were decoronated and enlarged up to F3 using the ProTaper Universal file system. After removing the apical 3 mm within the scope of endodontic surgery procedures, retrograde cavities were prepared with ultrasonic tips. The teeth were divided into three main groups according to the irrigation solution used: saline, 17% EDTA, and 9% HEDP. Following the irrigation of retrograde cavities, each main group was further divided into two subgroups in terms of using MTA Angelus and NeoPutty as retrograde filling materials. Bond strength values of hydraulic cements were measured by the push-out test. Fracture modes were examined under a stereo microscope. Two dentin sections from each group were examined under scanning electron microscopy (SEM) to observe dentinal tubules. Two-way ANOVA and post hoc Tukey tests were used to analyze the data. Results. Irrigation solutions similarly affected the bond strength values of hydraulic cements (P=0.115). MTA Angelus showed significantly higher values than NeoPutty in all the solution groups (P=0.34). Adhesive and cohesive fracture modes were mostly observed in the MTA Angelus and NeoPutty groups, respectively. Conclusion. EDTA, HEDP, and saline had a similar effect on the bond strength of hydraulic cements. The higher bond values of MTA Angelus compared to NeoPutty could support its safe use in endodontic surgery procedures.